1999
DOI: 10.1093/ajcn/69.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness, body composition, and all-cause and cardiovascular disease mortality in men

Abstract: The health benefits of leanness are limited to fit men, and being fit may reduce the hazards of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
467
3
18

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 854 publications
(507 citation statements)
references
References 30 publications
19
467
3
18
Order By: Relevance
“…These results support those found in adults. 11,42 Thus, fitness provides benefits even among adolescent subjects with a higher BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results support those found in adults. 11,42 Thus, fitness provides benefits even among adolescent subjects with a higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In adults, overweight and low levels of aerobic fitness are independently associated with an increased risk of CVD mortality. 10,11 It has thus been suggested that aerobic fitness should be considered in examining the relationship between body composition and chronic disease morbidity and mortality, as being aerobically fit may reduce the health consequences of obesity. 11,12 In children and adolescents, correlations are generally low (ro0.30) between aerobic fitness, body composition, and CVD risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of other prospective studies in men and women further suggest that high levels of physical activity protect against the incidence of coronary artery disease, independent of BMI, as well as other factors such as age, smoking, diabetes and hypertension (62). Furthermore, prospective analyses from the Aerobics Center Longitudinal Study have consistently reported that CRF is a significant predictor of mortality from all causes (9,10,63,64), CVD (9,10) and type 2 diabetes (65) in men and women, independent of BMI or WC. These relationships have been confirmed in older adults (66) and Canadian women (67).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 91%
“…Although exercise-induced weight loss is associated with attenuated CVD risk, several lines of evidence suggest that weight loss is not absolutely necessary to observe substantial benefit. First, it is well established that increasing physical activity and associated improvements in cardiorespiratory fitness (CRF) are associated with profound reductions in coronary artery disease and CVD mortality, independent of weight or BMI (9,10). Second, acute and chronic exercise is associated with substantial reductions in several cardiometabolic risk factors despite minimal or no change in body weight (11)(12)(13).…”
mentioning
confidence: 99%